TRANSFORMASI KETERAMPILAN DUKUN BAYI KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGNGI TRANSFORMASI KETERAMPILAN DUKUN BAYI KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGNGI - Irma Gus Tati Gus Tati; Daeng Ayub Natuna Ayub Natuna; Murni Baheram Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Absract : The problem of this study is "How can a midwife transformat skills to the next generation“. In accordance with the formulation of the problem, the purpose of this study was to determine the way of transforming midwife District of Hilir Regency Kuantan Kuantan Singingi. After research held , is expected to provide utility or benefits are: To add insight to the author on how to acquire the skills of a midwife, where these TBAs not obtain skills in a formal school. As suggestion for the Department of Health to contribute more in terms of coaching midwife to midwife know how to correct and proper in attending births. For required by those who need information regarding the TBAs. As sugestion for the TBAs to further enhance their knowledge in terms of attending births. The research site is in the District of Hilir Regency Kuantan Kuantan Singingi. This is a descriptive study with a qualitative approach that aims to provide a systematic overview of the state of the ongoing research on the object that is the model transformation skill birth attendants District of Hilir Regency Kuantan Kuantan Singingi. From interviews with informants, obtained information that the TBAs goal is to transform the skills that prospective midwife know reading or spell grammar along the way, other than that its purpose is to make candidates TBAs into future generations. The skills that are taught in these TBAs are reading along with the procedures that must be controlled at any given skill. The way TBAs get skill birth attendants is to thaught directly by the TBAs there are also prospective midwife visited through dreams. In terms of practice Carannya, midwife practicing midwife directly in front of the candidates. As for knowing or midwife assess whether candidates have mastered the skills, practicing midwife told her to direct her. If the midwife midwife felt the candidate has mastered its operation and its spell, akn midwife sent directly handle paasiennya and of course also accompanied by traditional birth attendants. Thus TBAs will determine the extent of control of the TBAs candidate against spells and skills procedures given. Keywords:  transformation, skills, TBAs